The analysis of unexpected death cases and emergency call system in one University Hospital - Sumikawa, Koji; Araki, Hiroshi; Yamashita, Kazunori; Nagatani, Atsuko; Cho, Sungsam (Japanese Journal of Reanimatology, 2014)
Hospitals are required to reduce unexpected inpatient death. In this retrospective study, we investigated patients who had died unexpectedly, and those who had received cardiopulmonary resuscitation (CPR) following a hospital emergency call (HEC) in our center within the previous year. The former and latter groups had 39 and 14 subjects, respectively, and approximately half of the total number of subjects had shown several signs of cardiopulmonary arrest (CPA). HEC had been requested infrequently for the former group, and those for whom HEC had not been requested showed a low rate of ROSC (return of spontaneous circulation). It was suggested that improvement in both the standards for requesting HEC and its administration may lead to an increase in the number of patients who can undergo intervention before developing CPA, and the ROSC rate.